Development of Module Sharaf Using a Deductive Approach in The Diniyyah Putri Lampung Boarding School - Mezan el-Khaeri Kesuma; Era Octafiona; Reni Puspita Sari (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2021)
This research aims (1) to produce a sharaf module on fi’l mujarrad and fi’l mazid’s material with a deductive approach that can be used as teaching material later, and (2) to test the feasibility of the product so it can be used effectively and efficiently. This research adopted the development research of Borg and Gall. This research was conducted at Diniyyah Putri Lampung Islamic Boarding School (PonPes), located in Negri Sakti Village, Gedong Tataan District, Pesawaran Regency, Lampung Province. The deductive approach in this module starts with the provision of rules that must be understood and memorized. Examples are given. After that, the students have been allowed to do exercises to apply the rules or formulas that have been given. Through seven stages of development, the researcher produced a product in the form of a sharaf module with a deductive approach at Ponpes Diniyyah Putri Lampung. The use of products in Sharaf modules developed in this study can make it easier for students to follow Sharaf subjects, especially in fi'l mujarrad and fi'l mazid materials, until students master the ability of qowa'id Sharaf.